2004
DOI: 10.1080/09595230410001704226
|View full text |Cite
|
Sign up to set email alerts
|

Pot, politics and the press—reflections on cannabis law reform in Western Australia

Abstract: Windows of opportunity for changing drug laws open infrequently and they often close without legislative change being affected. In this paper the author, who has been intimately involved in the process, describes how evidence-based recommendations to 'decriminalize' cannabis have recently been progressed through public debate and the political process to become law in Western Australia (WA). The Cannabis Control Bill 2003 passed the WA Parliament on 23 September. The Bill, the legislative backing behind the Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 28 publications
0
40
0
1
Order By: Relevance
“…Public opinion plays a crucial role in the political process (Lenton, 2004), and politicians and law makers now see cannabis as an issue that must be addressed in election campaigns. Most notably the issue has a clear role in the 2016 presidential election (Hudak, 2015, March 22).…”
Section: Politics and Public Opinionmentioning
confidence: 99%
“…Public opinion plays a crucial role in the political process (Lenton, 2004), and politicians and law makers now see cannabis as an issue that must be addressed in election campaigns. Most notably the issue has a clear role in the 2016 presidential election (Hudak, 2015, March 22).…”
Section: Politics and Public Opinionmentioning
confidence: 99%
“…The reasons for these changes are unclear, but some have suggested that where support has waned this may be due to macro-economic downturns and associated youth conservatism [20]; (4) in Australia, national opinion poll support for legalization of possession and use of cannabis declined from an early peak of 31% in 1984 to 25% in 1987 and then climbed steadily to a peak of 33% in 1993 where it remained until 2001, when it declined to 31% [18,19]; (5) recent National Drug Strategy Household Surveys put Australian support for legalising cannabis at 29% in 2001 and 27% in 2004 [21]; (6) the highest levels of support for legalizing cannabis among the Australian community come from those who have used cannabis, the young (18 -34 years), males, those looking for work, those with higher levels of education and voters on the left of the political spectrum [18]; (7) in Australia, public opinion polls indicate that support for the application of prohibition with civil penalties to minor cannabis offences has remained at between 45% and 49% between 1979 and 1987 [18,22], although in these surveys the terms are rarely explained.…”
Section: Why Study Public Attitudes To Cannabis Law?mentioning
confidence: 99%
“…The details of the scheme and the background to it have been described elsewhere [4]. They include: under the Cannabis Control Act (2003) adults who are apprehended for a minor cannabis offence have the option of paying a fine in full, or completing a specified cannabis education session, within 28 days of receiving a Cannabis Infringement Notice (CIN) in order to avoid a criminal charge.…”
Section: Introductionmentioning
confidence: 99%
“…Under the Cannabis Control Act 2003, WA became the fourth Australian jurisdiction to adopt a 'prohibition with civil penalties scheme' for minor cannabis offences when its Cannabis Infringement Notice (CIN) scheme came into effect on 22 March 2004 [1]. This study, described in full elsewhere [2], forms part of the prepost evaluation of the legislative reforms, aimed to measure the impact of the changes on attitudes and drug use of school children.…”
Section: Introductionmentioning
confidence: 99%